Positioning the role of universities and science diplomacy in advancing Indonesia’s sustainable development goals agenda - Anak Agung Mia Intentilia (Priviet Social Sciences Journal, 2025)
This study examines how Indonesian universities and the country’s evolving practice of science diplomacy jointly contribute to advancing the national Sustainable Development Goals (SDGs) agenda. Using a descriptive qualitative approach and relying on secondary data, this study analyzes the institutional roles, strategic initiatives, and policy frameworks that shape Indonesia’s SDGs implementation. The first part of the findings highlights the multidimensional role of universities through their core mandates of education, research, and community services. Universities are identified as key drivers of mainstreaming sustainability values into curricula, producing evidence-based research that informs policy, and implementing community outreach programs that directly address local development challenges. The second part explores Indonesia’s science diplomacy as an emerging tool for linking domestic scientific priorities to global platforms. Science diplomacy enables Indonesia to showcase local knowledge, attract international collaboration, and position its scientific innovations in global discussions on climate action, health security, and sustainable development. Together, universities and science diplomacy create complementary pathways to strengthen Indonesia’s SDGs ecosystem. The study concludes that integrating academic expertise with diplomatic engagement is essential for enhancing Indonesia’s global visibility and ensuring that local sustainability efforts contribute meaningfully to global SDGs targets.